Peroxiredoxin 1 induces inflammatory cytokine response and predicts outcome of cardiogenic shock patients necessitating extracorporeal membrane oxygenation: an observational cohort study and translational approach. Issue 1 (December 2016) - Liu, Chia-Hsiung; Kuo, Shuenn-Wen; Hsu, Li-Ming; Huang, Shu-Chien; Wang, Chih-Hsien; Tsai, Pi-Ru; Chen, Yih-Sharng; Jou, Tzuu-Shuh; Ko, Wen-Je
Abstract Background Extracellular peroxiredoxin 1 (Prdx1) has been implicated to play a pivotal role in regulating inflammation; however, its function in tissue hypoxia-induced inflammation, such as severe cardiogenic shock patients, has not yet been defined. Thus, the objective of this study was to test the hypothesis that Prdx1 possesses prognostic value and instigates systemic inflammatory response syndrome in cardiogenic shock patients undergoing extracorporeal membrane oxygenation (ECMO) support. Methods We documented the early time course evolution of circulatory Prdx1, hypoxic marker carbonic anhydrase IX, inflammatory cytokines including IL-6, IL-8, IL-10, MCP-1, TNF-α, IL-1β, and danger signaling receptors (TLR4 and CD14) in a cohort of cardiogenic shock patients within 1 day after ECMO support. In vitro investigations employing cultured murine macrophage cell lines and human monocytes were applied to clarify the relationship between Prdx1 and inflammatory response. Results Prdx1 not only peaked earlier than all the other cytokines we studied during the initial course, but also predicted a worse outcome in patients who had higher initial Prdx1 plasma levels. The Prdx1 levels in patients positively correlated with hypoxic markers carbonic anhydrase IX and lactate, and inflammatory cytokines. In vitro study demonstrated that hypoxia/reoxygenation induced Prdx1 release from human monocytes and enhanced the responsiveness of the monocytes in Prdx1-induced cytokine secretions. Furthermore, functional inhibition by Prdx1 antibody implicated a crucial role of Prdx1 in hypoxia/reoxygenation-induced IL-6 secretion. Conclusions Prdx1 release during the early phase of ECMO support in cardiogenic shock patients is associated with the development of systemic inflammatory response syndrome and poor clinical outcomes. Thus, circulating Prdx1 provides not only prognostic information but may be a promising target against ischemia/reperfusion injury.